Applying Concepts and Tools in Demography for Estimating, Analyzing, and Forecasting Forced Migration. (September 2021) - Muttarak, Raya
Among demographic events (birth, death, and migration), migration is notably the most volatile component to forecast accurately. Accounting for forced migration is even more challenging given the difficulty in collecting forced migration data. Knowledge of trends and patterns of forced migration and its future trajectory is, however, highly relevant for policy planning for migrant sending and receiving areas. This paper aims to review existing methodological tools to estimate and forecast migration in demography and explore how they can be applied to the study of forced migration. It presents steps towards estimation of forced migration and future assessments, which comprise: (1) migration flows estimation methods using both traditional and nontraditional data; (2) empirical analysis of drivers of migration and migration patterns; and (3) forecasting migration based on multidimensional population projections and scenarios approach. The paper then discusses how these demographic methods and tools can be applied to estimate and forecast forced migration.